Associations between nutritional markers and inflammation in hemodialysis patients - Vannini, Franciele D. [UNESP]; Antunes, Aline A. [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Martin, Luis Cuadrado [UNESP]; Barretti, Pasqual [UNESP] (Springer, 2009)
The purpose of this study is to evaluate associations between clinical, laboratory, demographic, and nutritional markers with inflammatory state and malnutrition in hemodialysis (HD) patients. Fifty-two patients on regular HD were evaluated by clinical, demographic, laboratory, and nutritional parameters (food intake, anthropometric measurements, bioelectric impedance, subjective global assessment-SGA and appetite characteristics). Inflammation (serum C-reactive protein a parts per thousand yen 0.9 mg/dl) was present in 13 (25%) and malnutrition (SGA) in 16 (30.7%) patients. Body mass index (BMI), total lymphocytes count, and phase angle were negative and independently associated with malnutrition. Values of BMI a parts per thousand yen 25 kg/mA(2) were associated with diabetes, positively associated with adipose tissue percentage (BIA) and negatively associated with diastolic blood pressure. Phase angle was positively associated with hematocrit, total lymphocytes count and serum creatinine, and was negatively associated with age. A negative and independent association between muscle mass percentage (BIA) and inflammation was observed. These results suggested that inflammatory state induces muscle mass depletion, while high BMI is associated with diabetes and with lower diastolic blood pressure, a recognized cardiovascular risk factor in uremic patients. Phase angle and SGA were associated with traditional nutritional markers, reinforcing their validity for HD patients.
Keywords: Malnutrition; Inflammation; Hemodialysis; Chronic renal failure; Malnutrition-inflammation atherosclerosis syndrome